Hand dimensions and dominant handgrip strength (DHGS) among Bangladeshi female laborers and non-laborers (Asian Journal of Medical and Biological Research, 2025)
Hands are vital tools for work, playing a crucial role in performing diverse manual, functional, and skilled tasks necessary for occupational and daily activities. Their morphology and functional properties are important determinants of physical performance. Dominant handgrip strength (DHGS) is a straightforward and cost-effective measure that offers valuable insights into the condition of muscles, nerves, bones, and joints, and also reflects general body strength. The objective of this study was to assess the association between DHGS and designated hand dimensions among adult Bangladeshi female laborers and non-laborers. It was hypothesized that larger hand dimensions would be positively associated with higher DHGS. A total of 100 healthy females (50 laborers and 50 non-laborers) living in various slums of Dhaka city, Bangladesh, participated in this cross-sectional study conducted from March 2019 to February 2020. Right-hand dimensions and DHGS were measured using standardized tools and protocols according to the study methodology. Data were analyzed using Pearson’s correlation coefficient. Among laborers, DHGS showed significant positive correlations with most hand dimensions, including hand breadth (r = 0.398), wrist breadth (r = 0.493), and hand span (r = 0.388) (P < 0.01). In non-laborers, significant correlations were found with hand breadth (r = 0.291), palm breadth (r = 0.330), and wrist breadth (r = 0.504). DHGS was positively associated with most hand dimensions in both groups, and female laborers had significantly greater handgrip strength and hand measurements than non-laborers. These findings provide useful baseline data for clinical assessment, rehabilitation, and ergonomic tool design for women.Asian J. Med. Biol. Res. 2025, 11(4), 97-103